Recria de novilhas de corte em pastagem natural sob pastoreio contínuo e rotativo no outono-inverno - Soares, Émerson Mendes (2014)
The natural grasslands of the Pampa Biome has been the forage base to the livestock at the Rio Grande do Sul state for over three centuries. However, the studies relative to primary and secundary production are still, relativelly recents which, consequently, reflected in lower productives indices in this grasslands. The aim of this work was to evaluate the beef heifers' performance, at pre-mating stage, in two grazing methods using the sward height as the grazing intensity criteria. The treatments were two grazing methods (continuous and rotational) in a natural grassland at autumn-winter period with a same grazing intensity. The tester animals were beef heifers with initial age of 17 months and initial body weight of 258 kg. Evaluated variables were available forage mass (AFM), available forage on offer (AFF), height of the lower stratum (HLS), crude protein (CP), neuter detergent fiber (NDF), in situ organic matter digestibility (ISOMD), total digestible nutrients (TDN), average daily gain (ADG), body condition score (BCS), reproductive trait score (RTS) and stocking rate (SR). There was no interaction treatments×periods for any investigated variable. AFM and HLS were decreasing and the AFF was similar over time. CP and NDF were similar over time and ISOMD and TDN decreasing. The ADG was positive only at third experimental period while that BCS, RTS and SR decreasing over time. The animal performance achieved did not enable the corporal and reproductive development conditions to provide the mating of the heifers.